Enhancing Hydrogen Storage Properties of Metal Hybrides Enhancement by Mechanical Deformations - Huot, Jacques (SpringerBriefs in Applied Sciences and Technology, 2016)
This book shows how severe plastic deformation techniques could be used to enhance the hydrogen storage properties of metal hybrides. The mechanochemical techniques of ball-milling (BM), Cold Rolling (CR), Equal Chanel Angular Pressing (ECAP) and High Pressure Torsion (HPT) are covered. Each technique is described and critically assessed with respect to its usefulness to process metal hybrides at an industrial scale.